GMP-Compliant Universal Antigen Presenting Cells (uAPC) Promote the Metabolic Fitness and Antitumor Activity of Armored Cord Blood CAR-NK Cells - Liu, Enli; Ang, Sonny O. T.; Kerbauy, Lucila; Basar, Rafet; Kaur, Indreshpal; Kaplan, Mecit; Li, Li; Tong, Yijiu; Daher, May; Ensley, Emily L.; Uprety, Nadima; Nunez Cortes, Ana Karen; et al. (Frontiers in Immunology, 2021)
Natural killer (NK) cells are innate lymphocytes recognized for their important role against tumor cells. NK cells expressing chimeric antigen receptors (CARs) have enhanced effector function against various type of cancer and are attractive contenders for the next generation of cancer immunotherapies. However, a number of factors have hindered the application of NK cells for cellular therapy, including their poor in vitro growth kinetics and relatively low starting percentages within the mononuclear cell fraction of peripheral blood or cord blood (CB). To overcome these limitations, we genetically-engineered human leukocyte antigen (HLA)-A− and HLA-B− K562 cells to enforce the expression of CD48, 4-1BBL, and membrane-bound IL-21 (mbIL21), creating a universal antigen presenting cell (uAPC) capable of stimulating their cognate receptors on NK cells. We have shown that uAPC can drive the expansion of both non-transduced (NT) and CAR-transduced CB derived NK cells by >900-fold in 2 weeks of co-culture with excellent purity (>99.9%) and without indications of senescence/exhaustion. We confirmed that uAPC-expanded research- and clinical-grade NT and CAR-transduced NK cells have higher metabolic fitness and display enhanced effector function against tumor targets compared to the corresponding cell fractions cultured without uAPCs. This novel approach allowed the expansion of highly pure GMP-grade CAR NK cells at optimal cell numbers to be used for adoptive CAR NK cell-based cancer immunotherapy.